Model-based Performance Analysis of Hydropurification Reactor - Chai , Kah Sin (IRC, 2016)
Hydrotreating processes are commonly utilized in the industry to improve the purity of product by removing the impurities. This project focuses on the performance analysis of the hydropurification trickle bed reactor. In this research, the process of hydropurification of terephthalic acid is studied, and the evaluation of the reactor performance is carried out employing different reactor models. Crude terephthalic acid (CTA) is a product of the oxidation of p-xylene (PX) including some impurities such as 4-carboxybenzaldehyde (4-CBA) and p-toluic acid (PT). These impurities contaminate the terephthalic acid (TA) and must be removed to avoid difficulties in the operation control of the downstream process and low quality of the final product. The most important impurity of the CTA powder is 4-CBA, which its existence in terephthalic acid causes some problems in the control of the polymerization process of the downstream plants which utilize PTA as raw material.